A educação financeira como ferramenta educativa frente ao consumo alimentado pelas agências financeiras - Mota, Fábio Lemos (2019)
The general objective of this thesis was to study the indebtedness and the role of educative-financial practices, in order to evaluate how these practices can combat the strategies of stimulus to the consumption and the indebtedness of the people, used by financial capital. Its specific objectives were: a) To discuss the key concepts of the financial system and the internationalization and financialization of capital; b) Present data about indebtedness of the population, financial system and financial education; c) Discuss the deregulation of the national financial system; d) Reflect about the possibilities and effectiveness of the use of financial education in counterpoint to indebtedness as a contradiction of capital. Methodologically, the descriptive research and the qualitative and quantitative nature were used and taking as a method of analysis the dialectical critic. Notes that in Brazil there is a growing indebtedness of local population, which is encouraged by national legislative changes that allowed the increase of interest rates on credit operations. It has links with the process of internationalization of international financial capital, which cause a series of effects on national financial systems, that needed to promote a set of measures aimed at increasing corporate profit rates and consequently generate consumer losses and contribute for your indebtedness. The research found that the actions developed by the National Strategy for Financial Education are aligned with the conceptions of education and Financial Education and are guided by international organizations, aiming at developing a set of skills to minimize the negative impacts generated by consumerism. In this sense, it argues that financial education should contribute to the understanding that exacerbated consumerism is a fetish produced by the capitalist system. For this to happen, it will have to relate the financialization of international capital, globalization and neoliberalism, starting with its evolution, historicity and interfaces with the development of the capitalist mode of production.